Design of Zero Energy Building and its Energy Management - J. Vijay, V. Vanitha, G. Janakiraman, S. Lokeshwaran, D. Sriram (International Journal of Advanced Science and Technology, 2020)
A zero-energy building (ZE), is alternately called as zero net energy (ZNE) building, a building with zero net energy consumption, which means the entire quantity of energy employed by the building on an associate annual basis is capable the quantity of renewable energy created on the positioning or in different definitions by renewable energy sources offsite. In some cases, these buildings consequently contribute less overall gas to the atmosphere throughout operations than similar non-ZNE buildings. The challenge in Zero-energy building (ZEB) style is to seek out the most practical combination of style methods that might face the energy performance issues of a selected building. In this paper, we tend to discuss the residential building description as a way to build renewable energy sources so that the building will utilize the energy generated by renewable sources. Therefore it satisfies the ideas of Zero-energy building. Also the energy management so that the created energy is maintained in efficient way without wasting.